Hubungan Tingkat Pengetahuan Terhadap Perilaku Menjaga Kesehatan Gigi pada Siswa Kelas IV-VI SDN Mranggen - Febriana, Lady Ayu; Husain, Fida' (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The most dental health problems in Indonesia are damaged/cavities/pain by 54%. The high number of dental health problems is influenced by several factors, one of which is knowledge and behavior factors that have not realized the importance of maintaining dental health. Knowing the relationship between the level of knowledge on the behavior of maintaining dental health in children in grade IV-VI students at SDN Mranggen Polokarto Sukoharjo. This research is a quantitative research using a cross sectional approach method. The total population is 247 students and the sample is 71 grade IV-VI students at SDN 1 Mranggen, SDN 2 Mranggen, and SDN 3 Mranggen Polokarto Sukoharjo. Data collection using questionnaire with analysis test using Spearman Rho. obtained knowledge level of 78.9% good category and behavior of 66.2% medium category and analysis results obtained P.Value of 0.014 (< 0.05). Based on the results obtained, it was concluded that there was a relationship between the level of knowledge on the behavior of maintaining dental health in grade IV-VI students of Mranggen Polokarto Sukoharjo State Elementary School.